(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Sulung CAVT, Chair NE, Rahayu DA, Nugroho ED, Rusdianto. 2024. Morphology and COI barcodes reveal local loaches (Nemacheilus spp.) from Pasuruan River, East Java, Indonesia. Biodiversitas 25: 2806-2819. The family Nemacheilidae is one of the most diverse and widespread family of freshwater fishes. The nemacheilid loach in the Pasuruan river is relatively abundant; however, there is limited information available about this species. Therefore, further research is necessary to identify loaches from the Pasuruan area. This research aimed to identify the local loach species from Pasuruan District. The pectoral fins were stored in pure-grade ethanol and subjected to DNA extraction, polymerase chain reaction (PCR), and sequence analysis using bioinformatics tool, BOLD systems, and Automatic Barcode Gap Discovery (ABGD) web. The morphological identification revealed two local loaches, Nemacheilus chrysolaimos Valenciennes 1846 and Nemacheilus fasciatus Valenciennes 1846. The high haplotype diversity (Hd) of 0.9 and nucleotide diversity (?) of 0.1 indicate a wide range of genetic variations. The frequency of parsimony informative sites at 25.6% and 16 polymorphic sites and the overall ts/tv ratio of 2.3. The phylogenetic trees demonstrated a clear and unambiguous branching pattern for N. fasciatus and N. chrysolaimos forming their own monophyletic branches. Kimura’s 2-parameter genetic distance of the COI gene sequences between these two species was 0.11. This finding was strengthened by morphological and molecular identification results, which indicated that there are two local loach species in Pasuruan District.